Inoculação e coinoculação de microrganismos via semente e sulco de semeadura na soja em terras baixas - Nunes, Rafaela Leopoldina Silva (2023)
Soy cultivated in lowland areas is constantly expanding, being rotated in the rice soils of Rio Grande do Sul, mainly due to the economic appreciation and benefits generated by rice. However, in lowlands soybeans can be affected by various stresses, so it is essential to adopt integrated physical, chemical and biological tools to solve agricultural problems. The use of bioinputs can help with biological nitrogen fixation, promoting plant metabolism, reducing incidences of diseases, among others. However, the way in which it will be made available may influence its efficiency. With this, the objective was to evaluate the effects of inoculation and coinoculation of Bradyrhizobium japonicum with multifunctional microorganisms in soybean crops, and the best way to apply them via seed treatment and sowing furrow in lowland environments. In the first chapter, an experiment was carried out in a greenhouse, in the Várzea experimental teaching area at UFSM, using a completely randomized experimental design, with four replications and ten treatments: 1) Control; 2) Bradyrhizobium japonicum (Bj); 3) Bj + A. brasilense; 4) Bj + T. asperelloides; 5) Bj + P. fluorescens; 6) Bj + B. subtilis; 7) Bj + B. pumilus; 8) Bj + B. amyloliquefaciens; 9) Bj + B. megaterium; 10) Bj + Bio bokashi. At 50 days after installation, biometric, physiological and chemical evaluations were carried out on the plants. The results identified that the inoculation and co-inoculation of microorganisms does not affect the aerial part and the NPK levels of the plant leaf tissue, but positively influences the root system. Inoculation of B. japonicum presents an average increase of 60.8% in root dry mass (MSR), 60.7% in the number of nodules (NN) and 66.6% in root volume (VR), also presenting greater net carbon assimilation rate and water use efficiency. Coinoculation with other bacteria stimulates a greater supply of dry root mass in plants, with emphasis on A. brasilense, which increased MSR, NN and VR when compared to simple inoculation, making it a good choice for coinoculation. In the second chapter, two field experiments were carried out, one in the municipality of Santa Maria-RS and the other in Candelária-RS, using a randomized block experimental design in a split plot, bifactorial 2 x 8, with four replications. Two forms of application were distributed in the main plots: (seed and sowing furrow) and in the subplots eight associations between microorganisms: 2) Bj; 3) Bj + A. brasilense; 4) Bj + T. asperelloides; 5) Bj + P. fluorescens; 6) Bj + B. subtilis; 7) Bj + B. amyloliquefaciens; 8) Bj + B. megaterium. Measurements of biometric, physiological and chemical variables in plants and grain productivity were carried out. With the main results obtained, it is observed that inoculation with B. japonicum is efficient and co-inoculation with bacteria, especially A. brasilense, has positive effects on the root system of plants, on the coverage rate of the vegetative canopy and on productivity. of soybeans, especially when applied in the sowing furrow.